O papel da estratégia de operações no processo de Internacionalização de empresas - Rodrigues, Tiago Cortes (2009)
Globalization related aspects, like the development of new technologies, volatility of capital and global actions of enterprises have increased competition in most market segments, demanding new postures and strategies from enterprises. In a global scenario, the strategy of internationalization adopted by companies has taken an extreme relevant part in the search of sustainable competitive advantages, which makes the operations strategy a function of extreme significance in this process. In this context, the present study was developed with the main objective of analyzing the role of the operations strategy in the process of internationalization of companies. Thereby, three internationalized companies of Ceara’s market that possess distinctive levels of internationalization were selected. A field search using semi structured interviews with directors and staff responsible for the strategy were used in the methodology, as well as secondary data. Results showed that the role of operations strategy is directly influenced by the way the company chooses to entry the international market. Furthermore, it was possible to find that the definition of competitive criteria aligned with the decision of different categories of operations strategy act as a supportive tool to the process of internationalization. One of the main conclusions was that the researched companies are still looking for a larger involvement of operations function in other areas of the enterprise. This would make operations function a central element of organization strategy, thus obtaining a competitive advantage and in that way upholding an internationalization process.